2018
DOI: 10.1590/0102-7786333016
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Irrigation Water Pumping by Remote Sensing: Application of the SAMIR Model to Citrus under Mediterranean Climate Conditions

Abstract: Agricultural intensification has led to overexploitation of water resources, in particular of the underground resource. Estimating groundwater exploitation remains a serious problem in arid and semi-arid countries such as Algeria. The objective of this work is to estimate volumes of pumped irrigation water using the SAtellite Monitoring of Irrigation (SAMIR) model from satellite imagery. Eleven (11) Landsat-TM images covering an area of 20 hectares of citrus orchards with a drip irrigation system were used. Ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…In order to improve the efficiency of water use in agricultural management, it is first necessary to calculate water requirement for irrigation needs form estimated crop water requirements and soil water balance, where crop evapotranspiration is the main component. Multispectral imagery of canopy reflectance and reference evapotranspiration can be directly converted into maps of potential crop water use [22], [23]. Hadjimitsis et al [19] have presented methodology for monitoring agricultural areas and estimating irrigation demand using satellite remote sensing, irrigation models, and spectroradiometric measurements.…”
Section: Geospatial Technology In Agriculturementioning
confidence: 99%
See 1 more Smart Citation
“…In order to improve the efficiency of water use in agricultural management, it is first necessary to calculate water requirement for irrigation needs form estimated crop water requirements and soil water balance, where crop evapotranspiration is the main component. Multispectral imagery of canopy reflectance and reference evapotranspiration can be directly converted into maps of potential crop water use [22], [23]. Hadjimitsis et al [19] have presented methodology for monitoring agricultural areas and estimating irrigation demand using satellite remote sensing, irrigation models, and spectroradiometric measurements.…”
Section: Geospatial Technology In Agriculturementioning
confidence: 99%
“…The results demonstrated potential of the remote sensing method and water balance models to determine spatial variations of actual evapotranspiration for an agricultural area, using data from any available satellite source at different scales, but complemented with routine meteorological measurement of air temperature, humidity, wind speed and sunshine duration. Tazekrit et al [23] showed that the demand of pumped irrigation water can be estimated from satellite images using the SAtellite Monitoring of Irrigation Model (SAMIR). Calculated volumes compared with measured data of pumped irrigation water for single year period show the difference of less than 10%.…”
Section: Geospatial Technology In Agriculturementioning
confidence: 99%